Strategy For Fulfilling Public Green Open Space in South Tangerang City - Muhammad Arief Rakhman; Janthy Trilusianthy Hidayat; Umar Mansyur (International Journal Labs, 2025)
South Tangerang City, a rapidly growing buffer zone for DKI Jakarta, faces increasing demands for spaces for economy, ecology, social interaction, sports, and recreation. To address this, expanding Public Green Open Space (GOS) is crucial. GOS serves ecological, social, cultural, aesthetic, and economic functions in urban planning. This study aims to: 1) analyze the adequacy and location of existing Public GOS in relation to the Spatial Plan (RTRW); 2) assess the potential land for additional GOS; and 3) formulate a strategy to increase the GOS area to 20% of the total city area. Using remote sensing, Weighted Sum Overlay, Analysis Hierarchy Process (AHP), and SWOT analysis, the results show that the current GOS area is 14.77% below the target, lacking 2,434 hectares to meet the 3,297-hectare target. The existing GOS covers 5.23% or 866 hectares. The potential to expand the GOS by 15.40% (2,539 hectares) would bring the total to 20.64% or 3,402 hectares. A defensive strategy is recommended to reduce weaknesses and avoid threats, including revising the RTRW to allocate at least 20% for Public GOS, creating regulations for green infrastructure and buildings, and promoting green economy programs.